Foreign Tourist Attitudes and Visit Intentions for Mountaineering Tourism in Pakistan - Nargis Dewan; Gwi-Gon Kim (Journal of Spatial and Organizational Dynamics, 2020)
The development of adventure tourism destinations through good service quality brought a new perspective for the perceptions of foreign tourists. This study analysed the impact of the attributes of tourism service quality (TSQ) - monetary advantages, convenience advantages, and safety and security - and tourists’ behavioural intention to engage in mountaineering in Pakistan. The study also analysed the moderating role of the destination’s image in creating the tourists’ intentions. A conceptual model was developed after the literature review. The research model was validated through exploratory factor analysis and Cronbach’s alpha values. The findings show that international tourists focus on the monetary and convenience advantages in their intentions to visit Pakistan. Personal safety and security had no significant impact on attitude, because tourists focused on mountaineering perceive “there is no way to avoid all risks”, although these risks can be minimized by taking courses and training in mountain climbing. Physical and environmental risks may occur because of travellers are unaware of the natural characteristics of the destination and their effects, just as personal risks may occur due to dangerous practices in leisure activities. The destination’s mountaineering image has a role in creating positive intentions to visit Pakistan in the near future.